Highly efficient perovskite solar cells with Ba(OH)2 interface modification of mesoporous TiO2 electron transport layer - Thambidurai, Mariyappan (2020)
Outstanding photovoltaic performances together with some advantageous fabrication methods are the driving forces for recent research in perovskite solar devices. Interfacial engineering greatly influences the overall performance of the organic–inorganic perovskite solar cell as it alters energy band alignment, carrier recombination, and charge extraction/transport. In this work, Ba(OH)2 was spun between the meso-TiO2 electron transport and organic–inorganic perovskite absorber layers to engineer the interface and enhance the photovoltaic performance. Ba(OH)2 modification shifted the conduction band of meso-TiO2 upward such that better alignment with perovskite energy level, reduced carrier recombination, enhanced optical absorption, and electron transportation were observed. These enhancements led to paramount power conversion efficiency (PCE) of 17.53% for optimum Ba(OH)2 concentration of 5 mg/mL spun on meso-TiO2 but poorer PCE of 16.08% for the devices without interfacial treatment. Through this study, we demonstrated the use of interface modification as a straightforward yet powerful approach to enhance performances of conventional perovskite solar cells.